Neonatal Sepsis: The Impact of Carbapenem-Resistant and Hypervirulent Klebsiella pneumoniae - Mukherjee, Subhankar; Mitra, Shravani; Dutta, Shanta; Basu, Sulagna (Frontiers in Medicine, 2021)
The convergence of a vulnerable population and a notorious pathogen is devastating, as seen in the case of sepsis occurring during the first 28 days of life (neonatal period). Sepsis leads to mortality, particularly in low-income countries (LICs) and lower-middle-income countries (LMICs). Klebsiella pneumoniae, an opportunistic pathogen is a leading cause of neonatal sepsis. The success of K. pneumoniae as a pathogen can be attributed to its multidrug-resistance and hypervirulent-pathotype. Though the WHO still recommends ampicillin and gentamicin for the treatment of neonatal sepsis, K. pneumoniae is rapidly becoming untreatable in this susceptible population. With escalating rates of cephalosporin use in health-care settings, the increasing dependency on carbapenems, a ‘last resort antibiotic’, has led to the emergence of carbapenem-resistant K. pneumoniae (CRKP). CRKP is reported from around the world causing outbreaks of neonatal infections. Carbapenem resistance in CRKP is largely mediated by highly transmissible plasmid-encoded carbapenemase enzymes, including KPC, NDM, and OXA-48. Further, the emergence of a more invasive and highly pathogenic hypervirulent K. pneumoniae (hvKP) pathotype in the clinical context poses an additional challenge to the clinicians. The deadly packages of resistance and virulence has already limited therapeutic options in neonates with a compromised defense system. Although there are reports of CRKP infections, a review on neonatal sepsis due to CRKP/ hvKP is scarce. Here, we discuss the current understanding of neonatal sepsis with a focus on the global impact of the CRKP, provide a perspective regarding the possible acquisition and transmission of the CRKP and/or hvKP in neonates, and present strategies to effectively identify and combat these organisms.